Prevalence of sexual dysfunction in patients with inflammatory bowel disease from a northeastern hospital in Brazil (Research, Society and Development, 2025)
Objective: To evaluate the prevalence of sexual dysfunction (SD) and the main associated factors in patients with inflammatory bowel disease (IBD) undergoing follow-up at the University Hospital of the Federal University of Sergipe. Methods: This is a cross-sectional study with 69 patients diagnosed with Crohn's Disease (CD) or Ulcerative Colitis (UC) of both sexes who have had previous sexual intercourse and are undergoing outpatient follow-up. Clinical and epidemiological aspects were evaluated and the Female Sexual Function Index and the International Index of Erectile Function were applied. The Student's t test was used for parametric analysis between continuous variables, and the Mann-Whitney test for non-parametric analysis. To verify the association between categorical variables, the chi-square test or, if necessary, Fisher's exact test was used. The BioEstat 5.0 software, with free distribution, was used, considering a statistical significance interval of 95%. Results: of the 69 patients, 39 (56.5%) were women, with a mean age of 38 ± 12.2 years. The overall prevalence of SD was 59.4%, with a predominance among women (82%). There was no difference in the mean scores between the phenotypes, and there was no correlation between age or time of diagnosis. A positive association was found between SD and the presence of seton (p = 0.032) among women. Conclusion: the prevalence of SD was high among patients with IBD assisted by the tertiary center, especially among women, being associated with the use of a seton in this group.